Monetary Policy and Inequality - Asger Lau Andersen; Niels Johannesen; Mia Jørgensen; José-Luis Peydró (ZBW - Leibniz Information Centre for Economics, 2021)
We analyze the distributional effects of monetary policy on income, wealth and consumption. We use administrative household-level data covering the entire population in Denmark over the period 1987-2014 and exploit a long-standing currency peg as a source of exogenous variation in monetary policy. We consistently find that the gains from softer monetary policy in terms of income, wealth and consumption are monotonically increasing in the ex ante income level. The distributional effects reflect systematic differences in exposure to the various channels of monetary policy, especially non-labor channels (e.g. leverage and assets). Our estimates imply that softer monetary policy increases income inequality by raising income shares at the top of the income distribution and reducing them at the bottom.
Keywords: E2; E4; G1; G2; G5; 330; Monetary policy; Inequality; Household heterogeneity; Assets; Leverage